The Effect of Strengths-Based Performance Appraisal on Perceived Supervisor Support and the Motivation to Improve Performance - van Woerkom, Marianne; Kroon, Brigitte (Frontiers in Psychology, 2020)
Strengths-based performance appraisal focuses on identifying, appreciating, and developing employee’s qualities in line with the company goals. Based on self-determination theory (SDT), we hypothesized that strengths-based performance appraisals will bring about a stronger motivation to improve (MTI) performance, by making subordinates feel supported by their supervisor and thereby fulfill their need for relatedness. Moreover, we hypothesized that strengths-based performance appraisal will reduce the threat to the relationship between supervisor and subordinate when the performance rating is relatively low. To investigate our hypotheses, we distributed a questionnaire to employees working for a large Dutch consultancy firm right after their yearly appraisal (N = 422) and linked the questionnaire data to their official performance ratings. Conditional process analysis indicated that strengths-based performance appraisal had a positive effect on perceived supervisor support (PSS), and in turn on MTI performance. Furthermore, the effect of strengths-based performance appraisal was particularly strong, when the performance rating was relatively low. Our findings may inspire future research into strengths-based performance appraisal as a relational approach to employee development.